Petits diviseurs en dimension 1 - Yoccoz Jean-Christophe (Paris Societe Mathematique de France, 1995)
The dynamics of biholomorphisms in one complex variable near a fixed point is the subject of the first paper. In 1942, Siegel proved that such a germ is analytically linearizable if its linear part is a diophantine rotation ; the set of rotation numbers
Keywords: Diffeomorphisms